Fitnah in the Digital Age: Regulating Social Media Misuse Through Islamic Criminal Principles - Omar Saad Ahmed; Hussein Ajlan Hasan; Sameer Dawood Salman Bazool; Aigul Mirzaeva; Oudha Yousif Salman Al-Musawi (Institut Agama Islam Negeri Curup, 2025)
The global dissemination of fitnah false allegations, vilification, and damaging speech has become even more pronounced with the advent of social media, creating an ethical and moral quandary in many Muslim (and other) societies. Although most countries have adopted some version of secular laws for the control of their digital space, there remains a clear deficiency in the application of an Islamic criminal law that protects individual honor and social harmony. The study looks at the possibility of adapting the Islamic criminal principles to govern the abuse of social media platforms with special reference to offences similar to qadhf, ghibah, buhtan and namimah. It seeks to offer a jurisprudential model that is in harmony with the current digital situation but is also acceptable with Islamic legal principles. The article applies a doctrinal legal methodology and statistical scrutiny of 155 digital crimes that have been reported. Data were analyzed based on five dimensions of analysis: legal response, severity index, harm likelihood, public concern, and variation with the Shari‘ah compliance. Validation of the framework was guided by advice from jurists and organized classification of types of offense. Differences in legal enforcement and popular reaction are dramatic, according to the findings. The most compliant with Islamic law was False Accusation and the least verdict was Defamation (despite being the most frequent). Both Religious Incitement and Digital Harassment showed high potential for harm but were somewhat underregulated. Community responses conformed to Islamic ethics and, in many instances, were more sensitive than institutional responses. Possibilities for an ethically sound regulation of digital offenses under Islamic criminal law. A hybrid model combining the worldview values of Shari‘ah provisions and digital technology may potentially favor justice, accountability and social harmony on digital platforms.